Motives for non-medical prescription opioid (NMPO) use among young people in a semi-rural Canadian Province. (4th May 2022) - MacNeill, Lillian; Doucet, Shelley; Luke, Alison
ABSTRACT: Objective: In Canada, young people aged 15–24 had the fastest growing rates of hospitalization for opioid poisoning in the last decade, compared to other age groups. This cross-sectional study examined non-medical prescription opioid (NMPO) use in youth and young adults in a semi-rural Canadian province. Method: Participants completed an online survey about motives for NMPO use, and knowledge and utilization of local resources. Results: All participants (N = 108) were self-reported opioid users between the ages of 15–25 years. The majority of participants had been prescribed an opioid by a physician in the past. Regression analysis showed that being older, having an opioid prescription, and using opioids for pain, coping, or enhancement reasons predicted higher levels of disordered opioid use. Pain was the most common motive for NMPO use and the strongest predictor of disordered opioid use. Most participants reported having limited knowledge about harm reduction resources in their communities. Conclusions: Although the opioid crisis is a wide-spread concern, understanding why youth and young adults engage in NMPO use in local contexts may facilitate the development and implementation of resources that are more useful for these individuals, which could be scalable to other regions across Canada and internationally.